(untitled) (Международный научный журнал «Инженер», 2026)
The article discusses bridges, which are engineering structures designed to lay transport highways over natural and artificial water obstacles, and the technologies for their underwater construction. In particular, the technology of laying concrete mix using the VPT (vertical movable pipe) method, which is one of the important stages in the underwater construction of bridge foundations, is analyzed. The VPT method allows maintaining the quality of concrete in an underwater environment, ensuring its hydraulic properties and strength. This method is widely used in areas where groundwater flows under high pressure, drilled wells, pile foundations, and other structures. To prevent the separation and washing away of the concrete mixture, the stability of the water retention systems and the concrete at the end of the pipe is strictly controlled. The article also extensively covers the complexity of underwater and surface works, their technological and engineering features